National Household Survey on Drug Abuse, 2001 ([Verlag nicht ermittelbar], 2003)
The National Household Survey on Drug Abuse (NHSDA) series measures the prevalence and correlates of drug use in the United States. The surveys are designed to provide quarterly, as well as annual, estimates. Information is provided on the use of illicit drugs, alcohol, and tobacco among members of United States households aged 12 and older. Questions include age at first use as well as lifetime, annual, and past-month usage for the following drug classes: marijuana, cocaine (and crack), hallucinogens, heroin, inhalants, alcohol, tobacco, and nonmedical use of prescription drugs, including pain relievers, tranquilizers, stimulants, and sedatives. The survey covers substance abuse treatment history and perceived need for treatment, and includes questions from the Diagnostic and Statistical Manual (DSM) of Mental Disorders that allow diagnostic criteria to be applied. Respondents are also asked about personal and family income sources and amounts, health care access and coverage, illegal activities and arrest record, problems resulting from the use of drugs, and needle-sharing. Questions introduced in previous NHSDA administrations were retained in the 2001 survey, including questions asked only of respondents aged 12 to 17. These "youth experiences" items covered a variety of topics, such as neighborhood environment, illegal activities, gang involvement, drug use by friends, social support, extracurricular activities, exposure to substance abuse prevention and education programs, and perceived adult attitudes toward drug use and activities such as school work. Also retained were questions on mental health and access to care, perceived risk of using drugs, perceived availability of drugs, driving behavior and personal behavior, and cigar smoking. Questions on the tobacco brand used most often were introduced with the 1999 survey and have been retained through the 2001 survey. Demographic data include gender, race, age, ethnicity, marital status, educational level, job status, veteran status, and current household composition. In addition, in 2001 questions on purchase of marijuana were added.